2023
DOI: 10.1212/wnl.0000000000207339
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Dysfunction With Neuronal Injury in People With HIV on Long-Duration Antiretroviral Therapy

Abstract: BackgroundNeurologic outcomes in people with HIV (PWH) on long-duration antiretroviral therapy (ART) are not fully understood and the underlying pathophysiology is unclear. To address this, we established a cohort of such individuals and compared them to HIV-negative controls using a novel matching technique. Both groups underwent extensive cognitive testing, evaluation for psychiatric measures, and MRI and cerebrospinal fluid (CSF) analyses.MethodsParticipants underwent comprehensive neuropsychological (NP) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Regarding the other results, no previous studies have shown a clear association with ALT: in all fairness, the association we found is indeed statistically significant but with an OR of 1.02, which is a clinically insignificant increase. Another inconsistency with the literature—yet a controversial issue—[ 87 ] was the inverse relationship between cognitive impairment and duration of HIV infection (OR: 0.96), which is again statistically significant but almost clinically insignificant. In general, all the associations obtained, except for age and depression, failed to show ORs higher than ±10%.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the other results, no previous studies have shown a clear association with ALT: in all fairness, the association we found is indeed statistically significant but with an OR of 1.02, which is a clinically insignificant increase. Another inconsistency with the literature—yet a controversial issue—[ 87 ] was the inverse relationship between cognitive impairment and duration of HIV infection (OR: 0.96), which is again statistically significant but almost clinically insignificant. In general, all the associations obtained, except for age and depression, failed to show ORs higher than ±10%.…”
Section: Discussionmentioning
confidence: 92%
“…Chemokines IP-10/CXCL10 and RANTES/CCL5 in plasma have been found to correlate with and strongly predict NP performance, as measured by the GDS, in treatment-naïve PLWH [187,188]. Moreover, CSF TNFα levels remain increased even in PLWH on long-duration cART compared to matched controls [20]. Whether this pro-inflammatory milieu is directly involved in HIV neuropathogenesis or it is mediated by other comorbidities is an area of active research, with studies identifying a complex immune interplay between HIV infection and metabolic abnormalities, substance use, and even depression [42,189,190].…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…To be able to delve into the diagnostic methodologies, it is crucial to understand the nature of HIV-associated NCI. The common pattern of cognitive impairment, reported by numerous studies both before and after the cART era, has played a major role in guideline development for appropriate neuropsychological batteries [17][18][19][20]. NCI in PLWH is often referred to as having a "subcortical" pattern, with deficits predominately affecting executive functions, attention/working memory, speed of information processing, motor speed, episodic memory, and learning, while semantic memory, language, and visuospatial abilities are relatively preserved [12,18].…”
Section: Neuropsychological Assessments 21 Understanding Neurocogniti...mentioning
confidence: 99%